Comparison of Seismic Vulnerability Index Microzonation Using Usgs Vs30 Data and Microtremor Signal Measurements in Prambanan and Gantiwarno Sub-Districts, Klaten Regency: Perbandingan Mikrozonasi Indeks Kerentanan Seismik (Kg) Hasil Pengolahan Vs30 Usgs dengan Pengukuran Sinyal Mikrotremor di Kecamatan Prambanan dan Kecamatan Gantiwarno Kabupaten Klaten - Fajarningrum, Fitri; Wibowo, Nugroho Budi (Prodi Fisika Fakultas Sains dan Teknologi UIN Sunan Kalijaga Yogyakarta, 2024)
The May 27, 2006 tectonic earthquake that rocked the Bantul area of Yogyakarta and several areas in Central Java resulted in a lot of damage to buildings and casualties. Earthquake is a disaster that can be minimized by disaster mitigation, one of which is the seismic vulnerability index data of an area. This study aims to compare the microzonation of the seismic susceptibility index (Kg) as a result of measurement of microtremor signals by processing data Vs30 USGS. The data used were 30 microtremor signal measurement points and topographic models from the USGS website in Prambanan and Gantiwarno Districts, Klaten Regency. The calculation result of Vs30 USGS shows the value of seismic vulnerability index (Kg), which ranges from to . Meanwhile, the seismic vulnerability index value (Kg) results from the measurement of the microtremor signal, which ranges from to . Comparative graphs of data from measurements of microtremor signals with the results of processing Vs30 USGS produced R-values square small. This is due to several factors, namely the shift of measurement points with data points Vs30 USGS (longitude and latitude slightly shifted). In addition, the results of calculation of Vs30 USGS are based on the topography of the earth's surface which is limited to a depth of 30 meters so that it does not represent the results of measurement data directly.